Non-Agricultural Rural Employment and Rural Tourism, Bibliometrics of the Last 20 Years (2023)
The target of this excercise is to analize the investigation and scients documental´s production in conecction with the non-agricultural rural employment and the rural tourism, like an option of the economic´s dinamization for the local communities. It was a bibliometrics study to identify the structure of the concepts and ideas referent with the topic in the last 20 years through development of indicators that show us the impact and the productivity as result. Was analyzed the perspective and the level of productivity by the authors, thier influence zones, it means, the countries with the most numbers of publications and their participation in the different subsequent publications to their jobs through the identification of the once’s that were been aforementioned, the diffusion channels most common and the structure of the publications with the most important participation in the las two decades, principally with the articles of science investigation, their focusing and intentionality of this contributions to the topic. Finally, a short sounding through the use of a tool for the bibliometrics review, that let us know not only to identify the co-occurrence’s among the key words of the publications but also allow to visualize the different levels of interrelation and what are the main concepts and the appeal investigative on this area, but also project from other fronts the analysis of the social, economic and ambiental behavior.